Решить уравнение замены неизвестного
(3x-4)^2-5(3x-4)+6=0

Катя132211111 Катя132211111    1   03.12.2019 18:21    0

Ответы
dimonf dimonf  10.10.2020 18:11

ответ:2*((x+2)/(x-1))^2 -7 (x+2)/(x-1) +5=0

(x+2)/(x-1)=t              2t2-7t+5=0

                       D=7^2-4*2*5=49-40=9=3^2

                      t1=(7-3)/4=1; t2=(7+3)/4=5/2=2,5

(x+2)/(x-1)=1           ili      (x+2)/(x-1)=2,5

x≠1

x+2-x+1=0                      x+2-2,5x+2,5=0

решений нет                  -1,5х=-4,5; х=45/15; х=3

ответ: 3

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра